A case study of vibration monitoring in a dynamic compaction project - Hamidi, Babak; Nikraz, Hamid; Varaksin, S. (The Hong Kong Geotechnical Society and The Hong Kong Polytechnic University, 2011)
Dynamic Compaction is a well established ground improvement technique in which a heavy pounder is dropped from a significant height to improve the soil’s mechanical properties. The pounder impact creates waves that compact the ground; however these waves may also cause damage to neighboring structures and facilities. Peak particle velocity (PPV) has been determined as the most suitable method for assessing vibration associated risks. Previous researchers have proposed a number different equations for predicting PPV. In this paper PPV monitoring that has been carried out during Dynamic Compaction works at Fujairah Desalination Plant Phase 2 have been presented and compared to available equations. Some equations predict PPV values by a factor of up to 5 while others underestimate the measured values. Among the existing equations, the method that is able to most reliably overestimate PPV is identified. The authors also propose an alternative equation that appears to provide a better estimation of the particle velocity.